Pattern of Suicidal Deaths in Belagavi: Retrospective Study (Medico Legal Update, 2021)
A retrospective study was undertaken over a period of 3 years to find out pattern of suicidal deaths inBelagavi. Autopsied at BIMS Hospital, a referral District hospital catering to the needs of public within aradius of 150 km. Out of 2200 autopsies conducted, 670 were suicidal deaths.The commonest age group of victims were 21-40 yrs. Males predominated females in the ratio of 3:1.Maximum number of victims belonged to rural area. Majority of the victims were married. Common mode ofsuicide was poisoning. Maximum victims were brought dead. Maximum numbers of victims were farmers.Depression was the commonest cause for suicide.